Factors influencing Mortgage Redemption Performance for Microfinancing Ar Rahnu among B40 Entrepreneurs - Ismail, Mohammed ‘Izzuddin; Abdul Aziz, Nurzafreena; A Razak, Tengku Maaidah; Mohamed Yusof, Mohd Faiz (Environment-Behaviour Proceedings Journal, 2025)
Ar Rahnu has become an essential financial service in Malaysia, especially for B40 Entrepreneurs. However, the failure rate of mortgage redemption among B40 Entrepreneurs shows worrying figures. This study will identify the factors that affect mortgage redemption, such as business factors, borrower's attitudes towards their loans, other debt burden, and the amount of loans received. The theory of KAP is used as the focal theory. The empirical results of this study will help Ar Rahnu’s institutions and B40 entrepreneurs overcome mortgage redemption failures.